STUDIES ON THE ORGANIZATION OF THE BRUSH BORDER IN INTESTINAL EPITHELIAL CELLS : II. Fine Structure of Fractions of Tris-Disrupted Hamster Brush Borders - Overton, Jane (The Rockefeller University Press, 1965)
Two of the fractions obtained by density gradient centrifugation of Tris-disrupted brush borders from hamster intestinal mucosa have been identified as the microvillus cores and their surrounding membranous coats, respectively. This identification has the following morphological basis. In shadowed preparations one fraction (cores) appears as rounded, compact rods, and the other fraction (coats) appears as flattened sheets. Both rods and sheets have dimensions appropriate to the identities assigned to them. In addition, negative staining shows that the rods are composed of aligned particles of roughly 60 A, consistent with the appearance of the core in tissue section, where 60-A fibrils are characteristic. The sheets are covered by non-aligned particles of approximately the same size. Sectioned preparations show that the core fraction contains predominantly fibrous material with some membranous contamination and that the coat fraction is apparently composed exclusively of elongated sacs with a unit membrane structure. Some details of the structure of the core are evident in cases where the compact rod appears to be loosened, revealing a doubled strand. The strand is approximately 350 A wide; the compact rod is roughly twice this width. With negative staining the strand shows a dense central region. The morphological identification presented here is consistent with the distribution of enzymic activity among the density gradient fractions described in the preceding paper.